Peningkatan Kapasitas Pengelolaan Green Tourism Berbasis Lumbung Mataraman di Kalurahan Bendung, Semin, Gunungkidul, DIY - Unggul Priyadi (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2025)
INCREASING THE CAPACITY OF GREEN TOURISM MANAGEMENT BASED ON MATARAMAN BARN IN BENDUNG VILLAGE, SEMIN, GUNUNGKIDUL, DIY: The community service activity on the implementation of green tourism based on Lumbung Mataraman was carried out in Bendung Village, Semin Subdistrict, Gunungkidul Regency, DIY Province. The main objective of this activity was to create policies to encourage tourists to visit the Lumbung Mataraman educational tourist attraction, which is integrated with green tourism and food security, particularly through the aspects of governance and accommodation. The methods applied in the community service activity included mapping the problems faced and conducting a Focus Group Discussion. The results of the community service activity showed that the management of the Lumbung Mataraman educational tourism site is faced with the reality that tourists still spend very little time enjoying the educational tourism experience, so their spending has not been able to stimulate the local economy. On the accommodation side, the use of residents' homes as guesthouses continues, but improvements are needed to meet tourist comfort standards. The conclusion of this activity is to strengthen the strategic direction of visitor management to optimize tourist interest and the need to improve accommodation quality, such as the suitability of guesthouses. The recommended suggestion is for tourism managers to extend the length of stay of tourists through more effective management and quality accommodation, thereby increasing local economic contributions and strengthening the image of Lumbung Mataraman as a green tourism destination based on local wisdom. Regarding accommodation, managers can maintain service quality to enhance the impression and image of educational tourism among tourists.